Concentration of Serum Matrix Metalloproteinase-3 in Patients With Primary Biliary Cholangitis - Bauer, Alicja; Habior, Andrzej (Frontiers in Immunology, 2022)
Background and Aims Metalloproteinases (MMPs) are involved in many distinct processes in the liver. Matrix metalloproteinase-3 (MMP-3) plays an important role in connective tissue remodeling, degradation of collagen (types II, III, IV, IX, and X), proteoglycans, fibronectin, laminin, and elastin. In addition, MMP-3 can also activate other MMPs such as MMP-1, MMP-7, and MMP-9. Primary biliary cholangitis (PBC) is a cholestatic, autoimmune liver disease, characterized by the progressive destruction of intrahepatic bile ducts, leading to cholestasis, fibrosis, cirrhosis, and liver failure. Fibrosis is the result of an imbalance between production and degradation of the extracellular matrix surrounding hepatocytes. Our aim in the present study was to determine whether the measurement of serum MMP-3 is clinically useful for assessing ongoing liver fibrosis in patients with PBC. Methods The MMP-3 concentration was determined in 182 PBC patients and 80 non-PBC controls using a commercially available ELISA kit. Results Higher concentrations of MMP-3 were found in 61% of PBC patients. PBC subjects had greater MMP-3 levels than controls: 68.9 ± 62.6 vs 21.3 ± 7.4 ng/mL, p < 0.001 for healthy subjects; 68.9 ± 62.6 vs 22.7 ± 7.6 ng/mL, p = 0.022 for autoimmune hepatitis controls; and 68.9 ± 62.6 vs 37.2 ± 17.4 ng/mL, p = 0.002 for primary sclerosing cholangitis controls. The serum MMP-3 concentration was significantly elevated in patients with higher bilirubin concentration (107.6 ± 85.8 vs 61.6 ± 46.1 ng/mL, p < 0.001) and was correlated with the level of antimitochondrial antibodies specific for PBC. The concentration of MMP-3 in sera of PBC patients was also found to correlate with the state of liver fibrosis (OR = 4.3; p < 0.01). Conclusions Our study demonstrated significantly higher MMP-3 levels in PBC patients than in healthy and pathological controls. Increased MMP-3 concentrations were positively correlated with various clinical and immunological parameters, and advanced liver fibrosis. The level of MMP-3 was associated with hepatic dysfunction and could play a role in the pathophysiology of hepatic fibrosis in PBC.